The use of herbal medicines: a literature review (Research, Society and Development, 2022)
Phytotherapy is a method of treating diseases used for thousands of years, and with the advancement of time the interest in medicinal plants and natural remedies is increasing. Plants are natural and rich sources of pharmacological properties as they are composed of a wide variety of metabolites. As a result, herbal medicines are used by the population as a source of treatment for different diseases. Its use is based on traditional and popular knowledge, which is taught from generation to generation over the years, making it customary to use this method for the treatment of symptoms of some diseases. In Brazil, the use of phytotherapy is favored by the wide diversity of plants and especially the low cost in relation to other types of medicines, facilitating access for the poorest population. In recent decades, the country has faced several advances related to the regulation of herbal medicines and their acceptance as a therapeutic method available in the Unified Health System (SUS). The present study aims to propagate the benefits of herbal medicines, and also the need to raise awareness of their harm when used incorrectly. It should be added that, despite scientific advances, Brazil is a country that still needs to invest in the knowledge of its health professionals and in their research and studies on the subject.